Special issue: Health information transforming lives - Musoke, Maria G. N. (IFLA Journal, 2019)
The Health and Biosciences Libraries Section (HBS) of the International Federation of Library and Information Associations (IFLA) is the IFLA ‘voice’ on health and biosciences information and libraries. The HBS, therefore, acts as a forum for special libraries concerned with all aspects of information management and services in relation to the medical, health and other biological sciences. The HBS aims include: the implementation of and support for better management and provision of health care information to health practitioners, researchers, academics and consumers; facilitating the development and application of new technologies relevant to the health and biosciences libraries; supporting the next generation of health information professionals; strengthening and/ or initiating the cooperation between HBS and related libraries, organisations, institutions and associations at national, regional and international levels. The HBS, therefore, focuses on Sustainable Development Goal number 3.
Keywords: Health; health and biosciences; libraries; IFLA